Apoliprotein B metabolism in hamster livers, studied in vitro - Hayward, Nicola Margaret (Division of Medical Biochemistry and Structural Biology, 2018)
This study aimed to investigate lipoprotein metabolism in male hamsters fed diets considered to be atherogenic in humans. Livers from adult male hamsters were selected to study aspects of apolipoprotein B metabolism. Isolated hepatocytes in suspension were compared with those maintained under tissue culture conditions. Liver slices were also prepared and compared with isolated suspended hepatocytes. Freshly prepared hepatocytes from the animals were incubated with radiolabelled precursors in suspension, or they were maintained under tissue culture conditions; liver slices were also investigated. The rates of total protein synthesis were of the same order in each of these systems, but protein secretion was impaired in liver slices, probably as a result of diffusion problems associated with the altered architecture of the sliced tissue. Albumin constituted 40 - 50% of the secreted proteins in each system. The rates of VLDL synthesis were increased in cells and slices prepared from animals previously fed sucrose- or fat-rich diets, but the secretion of VLDL was inhibited when diets contained unsaturated fat. The overall synthesis of apolipoprotein B was enhanced by fat-feeding; in the case of suspended hepatocytes, secretion of this protein was decreased when the preceding diet contained fats that were unsaturated; while in the case of liver slices, secretion was paradoxically enhanced. Apolipoprotein B was not degraded at significant rates in hepatocytes prepared from either control or fat-fed hamsters.